Economics of healthy aging in India: A multidimensional perspective - Manzoor Ahmad Malik; S. P. Singh; Falguni Pattanaik (IZA Journal of Labor Policy, 2022)
Aging is the foremost challenge in recent times, given the demographic shift in populations across the world. It implies the costs of healthcare burden and involves economic and social security challenges through shortage of labor supply, consumption-saving paradox, increase in expenditure on healthcare, and most importantly, social capital among the developing countries. Furthermore, there is a likely challenge of old age security in terms of income and expenditure due to increasing healthcare costs and low earning incentives at older ages. India currently has the second largest population globally, with >9% of its population accounting for aging. Based on the multidimensional aging index (AI) using the latest longitudinal survey data of older adults in India, we examined the possible challenges of the economics of aging in India while examining the economic health and social outcomes of the elderly. Our results found that the elderly in India are highly exposed to negative impacts due to vulnerability in socio-economic and health spheres of life. Low labor force participation, lack of skills, and low literacy are the prevalent challenges faced by the elderly Indian population, particularly women. Similarly, the fiscal challenges include increased income tax and insurance coverage for the elderly, while health challenges imply a greater proportion of the disabled and multi-morbid, leading to more burden on the health and welfare system of India. Thus, given the possible short- and long-term effects of aging on the path of economic growth in India, policy incentives are required to minimize the impact and avert the burden of population aging in the country.
Keywords: J0; J1; J14; I15; 330; healthy aging; labor force participation; morbidity; health; well-being; economic burden